Effect of Terracing on Combating Soil Erosion by Water: Case Study In The Beribere Catchment, Northwest Ethiopia - Debie, Ermias; Singhb, K. N.; Belay, Mehretie (Ethiopian Journal of Social Sciences, 2018)
Accelerated soil erosion by water is a critical problem for Ethiopia, where population is rapidly growing and extensive farming systems are very common with little or no preventive measures. This paper presents the results of a study on the effects of terracing practices in reducing the magnitude of soil loss by using rill survey technique at cultivated field scales in relation to crop type and topographic position of the fields in the Beribere catchment, northwest Ethiopia. The study also assessed the factors accelerating rill erosion in the focused area. Rill erosion in the terraced fields was reduced by 53.5% as compared to the non-terraced control fields. In the terraced areas, terrace damages are the main contributing factors to soil loss due to rills. In the non-terraced fields, the slipage of concentrated runoff from up-slope areas and damage of drainage ditches were observed as the principal accelerating factors for the initiation and development of rill erosion, whereas they had insignificant effect for rill erosion in the terraced fields. Moreover, rill erosion shows spatial differences in terms of crop covers and relative topographic positions in the study site. Hence, there should be adequate platform to effective communication between farmers and extension staff to design site specific erosion control activities for addressing the problem. The study verifies that rill surveying is a significant method to pragmatic assessment for the effectiveness of terracing structures in arresting soil erosion by water.